Evolution of Shear Band in Plane Strain Compression of Naturally Structured Clay with a High Sensitivity - Bingheng Liu; Lingwei Kong; Chengsheng Li; Juntao Wang (Applied Sciences, 2022)
The formation of the shear band is associated with the failure of soil. However, there has been relatively little investigation on the evolution of shear bands in naturally structured clay with a high sensitivity. In this study, undrained plane strain compression tests, digital image correlation (DIC) analyses, and scanning electron microscopy (SEM) tests were performed to investigate the characteristics of shear bands in naturally structured clay. The basic mechanical properties and stress–strain relationships show that naturally structured clay exhibits a strong structure and high sensitivity. Compared with plane strain compression tests under low confining pressure, more localized shear bands emerge in the specimens during the tests under high confining pressures; however, when the specimens fail, only one shear band is fully developed, and the local deformation in the developed shear band is much larger than those in other localized shear bands. Moreover, the local stress–strain relationships inside and outside the shear band show distinct discrepancies. The SEM results show distinct micro-structures of clays inside and outside the shear band, which are caused by the development of the shear band. The findings in this work provide new insight into the failure of structured clay.